2013
DOI: 10.1111/1758-2229.12112
|View full text |Cite
|
Sign up to set email alerts
|

sigmaS, a major player in the response to environmental stresses in Escherichia coli: role, regulation and mechanisms of promoter recognition

Abstract: Bacterial cells often face hostile environmental conditions, to which they adapt by activation of stress responses. In Escherichia coli, environmental stresses resulting in significant reduction in growth rate stimulate the expression of the rpoS gene, encoding the alternative σ factor σ(S). The σ(S) protein associates with RNA polymerase, and through transcription of genes belonging to the rpoS regulon allows the activation of a 'general stress response', which protects the bacterial cell from harmful environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
177
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(190 citation statements)
references
References 113 publications
(161 reference statements)
13
177
0
Order By: Relevance
“…In addition, CsgD makes other connections with global regulators, thus diminishing the expression of FliA by alternative routes. For example, CsgD represses the transcription of DksA which, together with ppGpp, plays an important role in reorganizing gene expression in stationary phase, in particular by inducing the RpoS regulon (58). We also found that CsgD activates the transcription of ihfB (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, CsgD makes other connections with global regulators, thus diminishing the expression of FliA by alternative routes. For example, CsgD represses the transcription of DksA which, together with ppGpp, plays an important role in reorganizing gene expression in stationary phase, in particular by inducing the RpoS regulon (58). We also found that CsgD activates the transcription of ihfB (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Among them, the general stress response (GSR) 3 has been deeply studied in Escherichia coli (1)(2)(3). When E. coli is submitted to stressful life conditions including nutrient starvation in stationary phase, osmolarity variations, or pH modifications, the alternative transcriptional sigma factor of the GSR, S (also called RpoS), allows a reorganization of gene expression by controlling the S regulon that contains more than 500 genes.…”
mentioning
confidence: 99%
“…10), and heat (Table 2) stresses, S -dependent genes provide cross-protection against several different stresses. This cross-protection in E. coli occurs as a result of rpoS induction and S accumulation upon challenge with a specific environmental stress (40,74). Collectively, the results indicate that the multistress tolerance phenotype conferred by DR1558 is likely to be routed through RpoS in Ec-1558 cells.…”
Section: Discussionmentioning
confidence: 85%
“…This result emphasizes the fact that S levels are critically regulated in the cell, and a simple strategy, such as overexpression of the rpoS gene, cannot confer stress resistance. rpoS regulation in E. coli is highly complex and is modulated through different proteins, adaptors, and noncoding RNAs that affect the transcription, translation, and posttranslational stability of this gene (40,74). In these two studies (77,78), S accumulation was facilitated through the increased posttranslational stability of this protein in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation